Heart rate variability based on risk stratification for type 2 diabetes mellitus - Silva-e-Oliveira,Julia (2017)
ABSTRACT Objective To evaluate heart rate variability among adults with different risk levels for type 2 diabetes mellitus. Methods The risk for type 2 diabetes mellitus was assessed in 130 participants (89 females) based on the questionnaire Finnish Diabetes Risk Score and was classified as low risk (n=26), slightly elevated risk (n=41), moderate risk (n=27) and high risk (n=32). To measure heart rate variability, a heart-rate monitor Polar S810i® was employed to obtain RR series for each individual, at rest, for 5 minutes, followed by analysis of linear and nonlinear indexes. Results The groups at higher risk of type 2 diabetes mellitus had significantly lower linear and nonlinear heart rate variability indexes. Conclusion The individuals at high risk for type 2 diabetes mellitus have lower heart rate variability.